2010
DOI: 10.1016/j.ijheatmasstransfer.2010.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Study of bubble growth in water pool boiling through synchronized, infrared thermometry and high-speed video

Abstract: High-speed video and infrared thermometry were used to obtain time-and space-resolved information on bubble nucleation and heat transfer in pool boiling of water. The bubble departure diameter and frequency, growth and wait times, and nucleation site density were directly measured for a thin, electrically-heated, indium-tin-oxide surface, laid on a sapphire substrate. These data are very valuable for validation of two-phase flow and heat transfer models, including computational fluid dynamics with interface tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(129 citation statements)
references
References 18 publications
6
119
2
2
Order By: Relevance
“…In the growth stage of vapor bubble the regions with different heat transfer mechanism (microlayer region and area of dry spot in the center of nucleation site) appear. The boundary between different heat transfer modes is the triple contact line [2][3][4][5][6]. The area with a minimal temperature of the heater surface corresponds to microlayer region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the growth stage of vapor bubble the regions with different heat transfer mechanism (microlayer region and area of dry spot in the center of nucleation site) appear. The boundary between different heat transfer modes is the triple contact line [2][3][4][5][6]. The area with a minimal temperature of the heater surface corresponds to microlayer region.…”
Section: Resultsmentioning
confidence: 99%
“…With the use of PIV technique authors [5] analyzed the hydrodynamics of microflows at bubble appearance, growth and detachment from the surface. In recent years, a general method to study the evolution of temperature field under single vapor bubble is the high-speed infrared thermometry (IR) [3][4][5][6][7][8][9]. This technique allows to investigate not only integral heat transfer but also the main local characteristics at boiling such as nucleation site density, nucleation frequency, local heat transfer under vapor bubble, etc.…”
Section: Introductionmentioning
confidence: 99%
“…DEPIcT from the now-established IR thermometry technique with IR-opaque heaters (5/23) [Theofanous et al 2002, Wagner and Stephan 2009, Gerardi et al 2010, Kim et al 2012, where the temperature measured is the temperature of the surface, which makes it hard to identify phases on the surface conclusively.…”
Section: Description Of the Depict Techniquementioning
confidence: 99%
“…Using a high-speed infrared camera, Gerardi et al (2010) showed that the largest enthalpy required for bubble growth is transferred by microlayer evaporation during the saturated boiling of water. Gao et al (2012) also measured dynamic characteristics of the microlayer beneath an ethanol vapor bubble by using high-speed camera technique and laser interferometric method, while more recently Jung and Kim (2014) measured simultaneously the microlayer shape beneath a de-ionized water vapor bubble by using total internal reflection technique and the temperature distribution on the heating surface by a high-speed, high-resolution infrared thermometry.…”
Section: Introductionmentioning
confidence: 99%